1-[(Bromomethyl)(phenyl)methylene]-2-(2,4-dinitrophenyl)hydrazine - Salhin, Abdussalam (International Union of Crystallography, 2009)
The title compound, C(14)H(11)BrN(4)O(4), comprises two crystallographically independent molecules (A and B) in the asymmetric unit. In molecule B, intramolecular bifurcated N—H⋯O and N—H⋯Br hydrogen bonds and in molecule A, an intramolecular N—H⋯O hydrogen bond generate S(6) ring motifs. The dihedral angle between the phenyl and benzene rings is 5.44 (6) in molecule A and 7.63 (6)° in molecule B. The ortho- and meta-nitro substituents make dihedral angles of 6.67 (15) and 2.26 (15)° to the attached benzene ring in molecule A and 6.37 (17) and 5.81 (16)° in molecule B. The Br atom in molecule B is disordered over two positions with a refined site-occupancy ratio of 0.61 (3):0.39 (3). Interesting features of the crystal structure are the short Br⋯N [3.257 (3)–3.294 (4) Å], Br⋯O [3.279 (3)–3.307 (4) Å] and O⋯O [2.9319 (16)–2.9995 (16) Å] contacts, which are shorter than the sum of the van der Waals radii of these atoms. The crystal structure is further stabilized by intermolecular C—H⋯O and π–π interactions [centroid–centroid distances = 3.6643 (8)–3.8514 (8) Å].